Betelnus angel hair pasta / Dr Hazrina Ghazali … [et al.] - Ghazali, Hazrina; Karim, Shahrim; Othman, Mohiddin; Wan Hassan, Wan Melissa; Abdul Halim, Nurhasmilaalisa (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Pasta is a type of western dish which has gained its popularity for the past 10 years in Malaysia. Since the consumption of pasta is increasing, it is about time to introduce pasta that offers feature and characteristic by utilizing our own local plants. This pasta product is innovated by using two main ingredients which consists of Sireh (Piper Betel) and Pandan leaves (Pandanus Amaryllifolius). These two ingredients provide tremendous benefit in term of health such as contain strong anti-oxidative (Rathee et al., 2006) and give attractive aroma characteristics (Salim et al., 2003). The processing of this product involved several cooking methods (boiling, drying, cutting, etc).These local plants are widely grown in Malaysia and the usage are still limited to cooking foods at home. The innovation of this product will maximise the use of Sireh and Pandan leaves. This product is believed to be the first in Malaysia and it has a great potential to be commercialized in our food industry.